Partial Penectomy in a Horse with Paraphimosis - Rocha, Letícia Ramos; Ott, Leila Cardozo; Chenard, Marina Galindo; de Gouvêa, Liana Villela; Monteiro, André Rolim; Mendonça, Júlia de Souza; Barroso Lessa, Daniel Augusto; Helayel, Michel Abdalla (Acta Scientiae Veterinariae, 2021)
Background: In horses, an increase in the volume of penis and foreskin can be caused by trauma. The resultant edema interferes with the retraction of the penis and cause paraphimosis. Surgical intervention through penectomy is indicated in cases wherein an alternative treatment is not feasible. Partial penectomy can prolong the life and reproductive function of many stallions. The present study aims to report on the methodological, functional, and economic feasibility of a successful case of the use of Williams technique for partial penectomy performed in the field in a horse with paraphimosis, preserving urinary, productive, and reproductive functions. Case: A 10-year-old horse weighing 500 kg had clinical signs of paraphimosis due to the formation of granulomatous tissue following trauma to the glans region. A surgical intervention, namely a partial penectomy was decided to be performed to prevent injury from priapism. Due to the limited resources provided by the owner and the impossibility of moving the animal to a surgical center in a veterinary hospital, the procedure was performed in the field, with prior sanitization and preparation of the environment used to perform surgery. The horse was tranquilized with intravenous xylazine hydrochloride and acepromazine, with subsequent induction of anesthesia with ready-to-use (RTU) guaifenesin bolus and maintenance of anesthesia with an intravenous association of RTU guaifenesin, xylazine hydrochloride, and ketamine. The distal third of the penis was amputated using the recommended Williams technique. Although the complications like dehiscence and emergence of granulation tissue occurred after surgery, these were controlled in the daily follow-up of the animal and post-surgical treatment. Discussion:Paraphimosis predisposed the horse to abrasions and edema of the exposed portion of the penis. However, there was no urine retention, which suggested that the urethral ostium and the urethra had no lesions. Because the granulomatous lesions were located in the distal third of the penis and the extent of penile exposure was small, the partial penectomy technique proved effective in solving the permanent exposure of the penis. The anesthetic protocol used was inexpensive, easy to execute, and effective, and no anesthetic complications occurred, proving this protocol to be efficient for the anesthetic induction of animals in the field.In addition to being reliable and widespread, the Williams technique was recommended to prevent possible urethral stenosis and the development of contact dermatitis by urine. This technique makes a rapid recovery of the animal possible, with improvement of its physiological parameters, and due to ease of being able to be done in the field, it is also inexpensive. The edema and the granulation tissue that occurred after surgery were controlled with medication. In general, post-penectomy animals are not used for reproduction. This makes the present report an important contribution, because in cases in which the lesions present a distal disposition and the penile exposure is small, stallions have a chance of maintaining reproductive function after surgery, even with a long period of evolution before surgical treatment. This was demonstrated in the present case, as the animal in this case later impregnated a mare, with the pregnancy confirmed by ultrasound examination. Partial penectomy is a resolution technique for cases of traumatic paraphimosis, in which exuberant granulation tissue is formed in the distal third of the penis, with a long period of evolution. The surgery can be done in the field, with a low surgical cost to the owner, and a good productive and reproductive prognosis for the animal. Keywords: partial penectomy, paraphimosis, Williams technique, horse. Descritores: penectomia parcial, parafimose, técnica de William, equino. Título: Penectomia em equino com parafimose